Analisis faktor - faktor yang mempengaruhiReturn saham (studi empiris pada perusahaan manufaktur yang go public Di bursa efek indonesia tahun 2011-2014) - Prakoso, Rendy; , Dra. Nursiam, M.H., Ak., CA (2016)
This study purposes to examine the effect Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA), Price Earnings Ratio (PER), and Price To Book Value (PBV) of the stock retrun 2011-2014. The population used in this study manufacturing companies in Indonesia Stock Exchange in 2011-2014. The data used in this research is secondary data. Methods of sample return with a purposive sampling according to criteria that have been determined. The number of samples collected as many as 268 companies. The analysis was made by using multiple linear regression. These results indicated that (1) Current Ratio (CR) has no effect on the stock return ; (2) Debt Equity Ratio (DER) has no effect on the stock return (3) Return On Assets (ROA) had a significant affect on the stock returns ; (4) Price Earnings Ratio (PER) had a significant affect on the stock returns ; (5) Price to Book Value (PBV) has no effect on the stock return. This means that the high and low ROA, and PER can affect the level of stocks return.